Influence of rice straw incorporation and recommended dose of primary nutrients on growth, productivity and nutrient use efficiency of Rabi maize (Zea mays L.) - Raghava, Chabolu Venkata; Kalasare, Rajesh Shriram; Shankar, Tanmoy; Dash, Bishnuprasad; Sairam, Masina; Rishitha, Shaik (Plant Science Today, 2024)
Rice-maize-based cropping system is one of the important agricultural practices in India. Maize has a wider range of adaptability to various climatic and soil conditions, which allows the farmers to cultivate the crop at various locations throughout the year. During the present days, straw handling after rice crop harvesting has become a major problem to the farmers and the burning of rice straw is considered as a serious environmental threat causing air pollution. In this scenario, incorporation of rice straw in succeeding maize cultivation can be beneficial in various aspects like soil health improvement, increased productivity and proper waste management. Considering these, the present field study was conducted at the Post Graduate Research Farm of Centurion University of Technology and Management, Gajapathi, Odisha, India. The experiment was laid out in randomized complete block design with 8 treatments and each treatment was replicated 4 times. The details of the treatment are as follows, T1: absolute control, T2: 100 % RDF, T3: 100 % RDF + rice straw incorporation (RSI) at 2 t/ha, T4: 100 % RDF + RSI at 4 t/ha, T5: 100 % RDF + RSI at 6 t/ha, T6: 100 % RDF + RSI at 8 t/ha, T7: 75 % RDF + RSI at 2 t/ha and T8: 75 % RDF + RSI at 4 t/ha. The experimental results found that the superior values of growth attributes were obtained highest in treatments T2: 100 % RDF, T3: 100 % RDF + RSI at 2 t/ha. Further, the incorporation of rice straw at the rate of 2 t/ha (T3) accounted for maximum grain yield (6354 kg/ha), stover yield (8429 kg/ha) and biological yield (14783 kg/ha) of maize and this treatment remained at par with T2: 100 % RDF. The experiment concludes that application of the optimum dose of fertilizers (100 % RDF) along with the incorporation of 2 t/ha of rice straw can be recommended for better growth, yield and nutrient use efficiency of Rabi maize.